2016
DOI: 10.1002/slct.201600346
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Mesoporous Carbon Material (N-GMC) as a Highly Efficient Catalyst for Carbon Dioxide Fixation Reaction with Epoxides under metal-free condition

Abstract: A soft template (Brij‐35) controlled nitrogen‐doped mesoporous carbon material (N‐GMC) was prepared from glucose as a carbon source and melamine as a nitrogen source. The synthesized material was characterized by XRD, SEM, HRTEM, XPS, and Raman spectroscopy and nitrogen adsorption and desorption isotherms. Nitrogen enriches carbon material with high surface area and porous channel showed high CO2 fixation reaction at low temperature and ambient pressure. Excellent catalytic activity and reusability showed towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Cyclic carbonates have wide applications in the synthesis of organic and polymer intermediates, and as ingredients in pharmaceuticals and fine chemical industries . Many fruitful catalytic systems have been developed from this CO 2 fixation reaction and a wide range of catalysts has been developed for this chemical transformation …”
Section: Introductionmentioning
confidence: 99%
“…Cyclic carbonates have wide applications in the synthesis of organic and polymer intermediates, and as ingredients in pharmaceuticals and fine chemical industries . Many fruitful catalytic systems have been developed from this CO 2 fixation reaction and a wide range of catalysts has been developed for this chemical transformation …”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, three characteristics of carbon materials are of great importance: i) a moderately high surface area with suitable pore sizes would be beneficial to the exposure of active sites and transport of reaction substrates/products; ii) polar functional sites/groups grafted onto the pore walls are desirable to improve the interaction between the framework and CO 2 molecules; iii) active sites available for substrates and CO 2 are necessary. Based on previous reports, different acids, such as phenolic hydroxyl and carboxyl groups, ZnO species, etc., and Lewis bases such as pyridinic N, can be effective active sites . Particularly, the integration of acid and base sites into a single catalyst is favorable for the conversion of CO 2 by cycloaddition …”
Section: Methodsmentioning
confidence: 99%
“…On the basis of these catalytic results, we proposed the reaction mechanism as follows: As displayed in Scheme S1 to S3, the C−O bond of the epoxide can be first polarized by the phenolic hydroxyl groups, carboxylic acid or the Zn 2+ of ZnO (different acid sites) . At the same time, CO 2 can be activated by the pyridinic N or the O 2− of ZnO (Lewis base sites) . Then, the heterolysis of the C−O bond occurs by the nucleophilic attack of the halide anion on the less sterically hindered carbon atom of the epoxide.…”
Section: Methodsmentioning
confidence: 99%
“…According to pioneering work, a great number of synthesis strategies have been developed to prepare porous materials, including surfactant templating, colloidal crystal templating, polymer templating, and emulsion templating, among others [ 71 ]. Islam et al prepared a nitrogen-doped mesoporous carbon material ( N -GMC) by using glucose as a carbon source and melamine as a nitrogen source using the soft templating (Brij-35) method [ 72 ]. It was shown that a 98% yield of styrene carbonate could be obtained at 80 °C under 10 bar of CO 2 .…”
Section: The Biomass-based Catalyst Systems For Co 2 mentioning
confidence: 99%